OFR-47-75 Evaluation Of Mining Constraints To The Revitalization Of Pennsylvania Anthracite (The National Institute for Occupational Safety and Health (NIOSH), 1975)
The objective of this research was to evaluate the technical and economic constraints on the extraction and utilization of anthracite coal and to determine the research and development needed in order to make anthracite coal more fully utilized as a premium energy resource. In the report the contractor examines in detail the anthracite industry both past and present and evaluates market possibilities. Anthracite reserves and resources are analyzed and tabulated, and the problem of pumping and drainage from the flooded anthracite fields is covered. Current technology is considered in detail with a discussion of production techniques with potential for improvement. The contractor concludes the report with a summary of constraints on the anthracite industry and the contractor's recommendations for effecting a revitalization of that industry. An estimated production of 17 million tons annually by 1990 can be anticipated if adequate planning, research, and development to overcome present constraints are initiated in the near future.